Environmental impacts of the future supply of rare earths for magnet applications. (27th November 2020) - Langkau, Sabine; Erdmann, Martin
Abstract: The environmental impacts of rare earth mining have recently caused public concern, because demand for the rare earth elements neodymium (Nd), praseodymium (pr), dysprosium (Dy), and terbium (Tb) is expected to increase strongly as a result of their use in magnets for electric cars and other emerging applications. Therefore, we analyzed the future environmental impacts of producing these rare earth metals per kilogram and for global production in the year 2035 to obtain insights into their relevance and draw conclusions about suitable mitigation measures. We introduced a new stepwise approach that combines future scenarios of metal demand, policy measures, mining sites, and environmental conditions with life cycle assessment data sets. The environmental impacts of 1kg of Nd, Pr, Dy, and Tb will probably decrease by 2035. In contrast, the environmental impacts of the global production of these metals for magnet applications might increase or decrease depending on the development of demand and the environmental conditions of mining and production. Regarding mitigation measures, the attempts included in the Chinese consolidation strategy (improvement of the environmental conditions of mining, prevention of illegal mining) are the most promising to reduce impacts in the categories human toxicity, freshwater ecotoxicity and, in the case of Nd/Pr, also in eutrophication and acidification. For the remaining categories, reducing the increase in demand (e.g., by improving material efficiency) is the most promising measure. Enhancing the environmental performance of foreground processes has larger potential benefits than improving background processes for most impact categories, including human toxicity as the most relevant impact category following normalization. This article met the requirements for a gold‐gold JIE data openness badge described at http://jie.click/badges .